Implementation of Deep Learning in Improving Critical Thinking Skills (Case Study of SDN Pasawahan Kidul and SDN 3 Selaawi Purwakarta Regency) - Isny Yuniar; Fitriyah Maylani; Suharyanto H Soro (Civiliza Publishing, Indonesia., 2025)
This study aims to explore the implementation of deep learning in improving the critical thinking skills of elementary school students. The research was carried out at SDN Pasawahan Kidul and SDN 3 Selaawi Purwakarta Regency using a case study approach The research subjects included principals, teachers, and students. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. Data analysis is carried out interactively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that (a) the implementation of deep learning has been carried out through learning planning oriented to active student involvement; (b) Implementation of discussion-based, problem-solving, and simple project learning, as well as learning evaluation through formative assessments and authentic assessments; (c) Deep learning encourages students to express opinions, give reasons, analyze problems, and draw conclusions, thus contributing to the improvement of students' critical thinking skills. This study concludes that deep learning can improve the critical thinking skills of elementary school students supported by structured planning, consistent implementation, and evaluation oriented to critical thinking indicators.